In vitro and in vivo synergistic effect of chrysin in combination with colistin against Acinetobacter baumannii - Zhao, Yining; Liu, Yan; Feng, Luozhu; Xu, Mengxin; Wen, Hong; Yao, Zhuocheng; Shi, Shiyi; Wu, Qing; Zhou, Cui; Cao, Jianming; Zhou, Tieli (Frontiers in Microbiology, 2022)
Acinetobacter baumannii is an opportunistic pathogen that is primarily associated with nosocomial infections. With the rise in cases of acquired drug resistance, A. baumannii is gaining resistance to conventional antimicrobial drugs and even to the last line of antibiotics, such as colistin. Hence, the application of the synergistic combination of an antibiotic and a non-antibacterial agent is being contemplated as a new alternative therapeutic approach. Chrysin is a component of honey with anti-inflammatory and antioxidant properties. In this study, we evaluated the antibacterial activity of chrysin in combination with colistin against A. baumannii both in vitro and in vivo, as well as the cytotoxicity of chrysin with or without colistin. Our results revealed that chrysin and colistin exerted synergistic effects against A. baumannii by damaging the extracellular membrane and modifying the bacterial membrane potential. The chrysin/colistin combination group demonstrated an inhibitory effect on biofilm formation. In conclusion, it is expected that the synergy between these drugs can allow the use of a lower concentration of colistin for the treatment of A. baumannii infections, thereby reducing dose-dependent side effects. Thus, a combination therapy of chrysin/colistin may provide a new therapeutic option for controlling A. baumannii infections.